2016
DOI: 10.3855/jidc.7459
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between low serum vitamin D levels and HBV “a” determinant mutations in chronic hepatitis B patients

Abstract: Vitamin D deficiency is significantly associated with genotype B HBV "a" determinant mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…32 Additionally, our another studies observed that vitamin D deficiency was significantly associated with the mutation frequency of M133 in HBV infected patients, indicating that the obesity might lead to an increased risk of HBV vaccine-escape mutations. 33 …”
Section: Discussionmentioning
confidence: 99%
“…32 Additionally, our another studies observed that vitamin D deficiency was significantly associated with the mutation frequency of M133 in HBV infected patients, indicating that the obesity might lead to an increased risk of HBV vaccine-escape mutations. 33 …”
Section: Discussionmentioning
confidence: 99%
“…Genotypes C and B are the major causes of chronic hepatitis B and subsequent LC and HCC in East Asia[ 90 - 92 ]. Recent studies indicate that patients infected with genotype B had a higher prevalence of vitamin D insufficiency than those infected by the C genotype[ 23 , 93 ].…”
Section: Vitamin D Deficiency In Chronic Hepatitis B and Cmentioning
confidence: 99%
“…For example, a study by Huijuan Zhu et al. showed that genotype B virus is more affected by vitamin D [ 118 ]. This statement has been confirmed by other studies [ 119 ].…”
Section: Role Of Vitamin D In Immune Systemmentioning
confidence: 99%